MODERN APPROACHES TO ANTICOAGULANT THERAPY DURING CATHETER ABLATION TREATMENT OF NON-VALVULAR ATRIAL FIBRILLATION - E. A. Belikov; K. V. Davtyan; O. N. Tkacheva (Столичная издательская компания, 2015)
Prevention of thromboembolic complications in patients with atrial fibrillation during catheter pulmonary veins isolation is discussed. This subject review is presented with special consideration to new anticoagulants.